HIV/AIDS treatment and prevention in India : modeling the costs and consequences - Over, Mead (Health, nutrition, and population series, 2004)
This title projects the future implications of three alternative AIDS treatment financing policies for the health burden of AIDS in India and for its overall health expenditures. Written by an interdisciplinary team of AIDS experts, the book presents new data on the supply and demand for antiretroviral treatment in India and new models of the epidemiological effects and the financial costs of alternative policies